From Universal Price Subsidies to Modern Social Assistance : The Political Economy of Reform - World Bank (Washington, DC, 2014)
The efficiency and effectiveness of generalized subsidies as part of a safety net system are questionable. This is because generalized subsidies tend to create distortions in the food and fuel markets and are likely to be regressive and to suffer from significant leakage of benefits to the non-poor, diluting their impact on poverty reduction. They also often have higher administrative costs than cash transfers. The policy response to recent crises highlighted an emerging interest for a transition from food and fuel subsidies toward greater reliance on targeted cash transfer programs in several countries. The transition from a strong reliance on generalized subsidies to more modern and administratively more sophisticated social protection has been witnessed in much of the developing world as countries move from lower to middle income status. However, cutting back subsidies has social as well as political implications, and therefore needs to be managed and implemented appropriately. This paper seeks to examine the implications and aspects of subsidies reform, in particular the socio-political risk of cutting subsidies in the context of modernizing social assistance.